2023
DOI: 10.1021/acsomega.3c04565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Pressure, and Type of Gas Injected on the Formation and Decay of Mineral Oil-Based Foams

Erich T. Tiuman,
Fabrício S. da Silva,
Rigoberto E. M. Morales
et al.

Abstract: In three-phase gravity separators used in gas and oil production, foaming can occur by either depressurization or injection of gas in the equipment. This formed foam can be harmful, causing various problems such as liquid carry-over, gas carryunder, decreased capacity, and difficulty in level measurement. The mechanism of foam formation by gas injection in separators motivated the present study. Thus, this work proposes the analysis of the influence of certain physical−chemical parameters such as temperature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…Foam stability and pressure are interconnected, with foam generation affecting force on syringes. Szabries and colleagues 18 showed that higher pressure increases foam stability while Tiuman and colleagues 19 demonstrated that higher pressure promotes foam stability by generating smaller bubbles, minimizing Plateau borders, and slowing down Ostwald ripening. Hamza and colleagues 20 observed and explained a similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Foam stability and pressure are interconnected, with foam generation affecting force on syringes. Szabries and colleagues 18 showed that higher pressure increases foam stability while Tiuman and colleagues 19 demonstrated that higher pressure promotes foam stability by generating smaller bubbles, minimizing Plateau borders, and slowing down Ostwald ripening. Hamza and colleagues 20 observed and explained a similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%